Polarizer

The polarizer addresses the issue of iodine ejection and crack formation by forming specific low-concentration regions near the edge, resulting in enhanced durability and optical performance under heat shock conditions.

JP7654054B2Active Publication Date: 2025-03-31SUMITOMO CHEM CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023201324
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-11-29
Publication Date
2025-03-31
Estimated Expiration
2039-09-12

AI Technical Summary

Technical Problem

The polarizer described in Patent Document 1 has a low boric acid concentration region at the edge, leading to iodine ejection beyond 300 μm from the edge, which affects the polarizer's performance and reliability.

Method used

A polarizer with a resin film containing boric acid and iodine, where a low-boric acid concentration site and a low-iodine concentration region are formed near the edge, with specific dimensions and profiles to minimize iodine ejection and enhance durability.

Benefits of technology

The polarizer effectively suppresses iodine ejection and crack formation during heat shock tests, maintaining optical performance and design integrity, even when exposed to condensation heat shock conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654054000002
    Figure 0007654054000002
  • Figure 0007654054000003
    Figure 0007654054000003
  • Figure 0007654054000004
    Figure 0007654054000004
Patent Text Reader

Abstract

To provide a polarizer in which the occurrence of crack is suppressed in a dew condensation heat shock test in which a low-temperature (-40°C) dew condensation condition and a high temperature (85°C) condition are repeated, and a portion where iodine loss occurs in an end region of the polarizer does not become prominent.SOLUTION: A polarizer composed of a resin film containing boric acid and iodine is provided in which: a boric acid low density-portion where the concentration of boric acid is lower than the concentration of boric acid in an inside region inward 500 μm or more from the edge thereof is formed in a region that includes the edge in a plan view; an iodine low-density portion where the concentration of iodine is lower than the concentration of iodine in the inside region is formed in the region that includes the edge; and the length of the iodine low-density portion from the edge thereof is 19 μm or more and 100 μm or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polarizer, and also to a polarizing plate including the polarizer and a method for producing the same, and an image display device. [Background technology]

[0002] Patent Document 1 proposes a polarizer in which a portion having a lower boric acid concentration is formed at an end portion than at other portions. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2016-206641 A Summary of the Invention [Problem to be solved by the invention]

[0004] The polarizer described in Patent Document 1 has a portion with a low boric acid concentration at its edge, and in addition, iodine loss occurs over a width of more than 300 μm from the edge in a plan view ( FIG. 4( b )).

[0005] The object of the present invention is to provide a polarizer in which the occurrence of cracks is suppressed and areas where iodine loss occurs in the edge regions are not noticeable in a condensation heat shock test in which the polarizer is exposed to low-temperature (-40°C) dry conditions and cooled, then exposed to outside air at 25°C to cause condensation, and then exposed to high-temperature (85°C) dry conditions, and the like, and a polarizing plate having the polarizer and a method for manufacturing the polarizer and the polarizing plate. [Means for solving the problem]

[0006] The present invention provides the following polarizer, polarizing plate, image display device, and manufacturing method. [1] A polarizer that is a resin film containing boric acid and iodine, In a region including the end in a plan view, a low-concentration portion of boric acid is formed, the concentration of boric acid being lower than the concentration of boric acid in an inner region 500 μm or more inward from the end, A low iodine concentration portion having an iodine concentration lower than the iodine concentration in the inner region is formed in a region including the end portion, The polarizer according to claim 1, wherein the length from an end of the low iodine concentration portion is 19 μm or more and 100 μm or less.[2] The polarizer according to claim 1, wherein the concentration of boric acid in the low boric acid concentration portion decreases toward the end in a direction from the inside of the polarizer toward the end in a plan view. [3] The polarizer according to [1] or [2], wherein the length from the end of the low boric acid concentration portion is 15 μm or more. [4] The polarizer according to any one of [1] to [3], wherein the low boric acid concentration region and the low iodine concentration region are formed along an outer edge of the polarizer. [5] The polarizer according to any one of [1] to [4], wherein the polarizer has an irregularly shaped portion in a planar view, and the low boric acid concentration portion and the low iodine concentration portion are formed in an end region included in the irregularly shaped portion. [6] The polarizer according to [5], wherein the irregular portion is a concave portion provided in the peripheral portion or a through hole provided in the polarizer surface. [7] A polarizing plate comprising the polarizer according to any one of [1] to [6] and an optical film disposed on one or both sides of the polarizer. [8] An image display device comprising the polarizing plate according to [7]. [9] The image display device according to [8], having a camera hole.

[10] A method for producing a polarizing plate having a polarizer that is a resin film containing boric acid and iodine, and an optical film disposed on one or both sides of the polarizer, comprising the steps of: The method for producing a polarizing plate includes a base treatment step of contacting an edge of the resin film containing boric acid and iodine with a basic solution at a temperature of 50° C. or less for a period of 6 minutes or less.

[11] The method for producing a polarizing plate according to

[10] , wherein the basic solution contains water.

[12] The method for producing a polarizing plate according to

[10] or

[11] , wherein the basic solution is a solution in which a strongly basic compound is dissolved in a solvent.

[13] The method for producing a polarizing plate according to

[12] , wherein the strongly basic compound contains sodium hydroxide and / or potassium hydroxide.

[14] The method for producing a polarizing plate according to any one of

[10] to

[13] , further comprising a shaping step of shaping the resin film containing boric acid and iodine into a predetermined shape by cutting and / or punching, and subjecting the resin film after the shaping step to the base treatment step. Effect of the Invention

[0007] According to the present invention, it is possible to provide a polarizer in which the occurrence of cracks is suppressed and areas where iodine loss has occurred in the edge regions are not noticeable in a condensation heat shock test (hereinafter, for simplicity, simply referred to as a condensation heat shock test) in which the polarizer is exposed to low-temperature (-40°C) dry conditions and cooled, then exposed to outside air at 25°C to cause condensation, and then exposed to high-temperature (85°C) dry conditions, and the like, as well as a polarizing plate having the polarizer, and a method for manufacturing the polarizer and the polarizing plate. [Brief description of the drawings]

[0008] [Figure 1] 1 is a schematic cross-sectional view showing a polarizer according to one embodiment of the present invention. [Diagram 2] FIG. 4 is a schematic top view of a polarizer for illustrating a low concentration portion of boric acid. [Diagram 3] FIG. 4 is a schematic top view of a polarizer for illustrating a low iodine concentration portion. [Figure 4] FIG. 1 is a schematic cross-sectional view showing an example of an image display device having a camera hole. [Diagram 5] FIG. 2 is a schematic top view illustrating a polarizer according to one embodiment of the present invention. [Figure 6] FIG. 1 is a schematic plan view showing a polarizing plate according to one embodiment of the present invention. [Figure 7] FIG. 1 is a schematic plan view showing a polarizing plate according to one embodiment of the present invention. [Figure 8]FIG. 1 is a schematic plan view showing a polarizing plate according to one embodiment of the present invention. [Figure 9] 1 is a schematic cross-sectional view showing a polarizing plate according to one embodiment of the present invention. [Figure 10] FIG. 2 is a schematic diagram illustrating an example of a first laminate. [Figure 11] FIG. 4 is a schematic diagram showing an example of a second laminate and an end mill. [Figure 12] FIG. 4 is a schematic diagram showing an example of a cutting process. [Figure 13] FIG. 2 is a schematic diagram for explaining a measurement sample in the examples. [Figure 14] FIG. 2 is a schematic cross-sectional view showing a first laminate in an example. [Figure 15] FIG. 2 is a schematic top view showing a polarizing plate in an example. [Figure 16] 1 shows the results of TOF-SIMS analysis and edge observation in Example 1. [Figure 17] 4 shows the results of TOF-SIMS analysis and edge observation of Comparative Example 1. [Figure 18] 4 shows the results of TOF-SIMS analysis and edge observation of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, an embodiment of the present invention will be described with reference to the drawings, but the present invention is not limited to the following embodiment. In all the following drawings, the scale of each component is appropriately adjusted to make it easier to understand, and the scale of each component shown in the drawings does not necessarily match the scale of the actual component. In the drawings, equivalent components are given the same symbols. X, Y, and Z shown in each figure refer to three coordinate axes that are mutually orthogonal. The directions indicated by the XYZ coordinate axes in each figure are common to each figure.

[0010] <Polarizer> The polarizer is a resin film containing boric acid and iodine. The resin film containing boric acid and iodine may be, for example, a resin film in which iodine is adsorbed and oriented on a uniaxially stretched polyvinyl alcohol-based resin film, and polyvinyl alcohol molecular chains are crosslinked with boric acid. The polarizer may be an absorption-type polarizer that has the property of absorbing linearly polarized light having a vibration plane parallel to the absorption axis and transmitting linearly polarized light having a vibration plane perpendicular to the absorption axis (parallel to the transmission axis). The polarizer can be used as a polarizing plate by laminating an optical film to one or both sides with an adhesive or pressure-sensitive adhesive.

[0011] 1, a polarizer 2 can be disposed between a first optical film 3 and a second optical film 4 to form a polarizing plate 1. Hereinafter, the first optical film and the second optical film may be collectively referred to as optical films.

[0012] In the region including the end of the polarizer in plan view, a low boric acid concentration portion is formed in which the concentration of boric acid is lower than the concentration of boric acid in an inner region (hereinafter also referred to as an inner region) 500 μm or more inward from the end. In the inner region, the concentration of boric acid and the concentration of iodine can both be approximately uniform. As shown in FIG. 2, the polarizer 2 can have a low boric acid concentration portion 30 in the region including the end of the polarizer in plan view, and an inner region 32 500 μm or more inward from the end. The inner region 32 can include a region for displaying an image when incorporated in a liquid crystal display device. The boric acid concentration in the intermediate region 31 between the low boric acid concentration portion 30 and the inner region 32 is usually approximately the same as that of the inner region 32. In this specification, plan view means viewing from the thickness direction of the polarizer. The concentration of boric acid refers to the concentration of boric acid per unit area including the thickness direction of the polarizer, and is measured, for example, by time-of-flight secondary ion mass spectrometry (TOF-SIMS) which will be described in the Examples section below. In this specification, boric acid includes, for example, boric acid molecules (H3BO3) and borate ions (BO3 3- ) are included.

[0013] The polarizer having the low boric acid concentration portion tends to be less susceptible to cracking in a condensation heat shock test. The condensation heat shock test can be performed according to the method described in the Examples section below.

[0014] The concentration of boric acid in the low boric acid concentration portion is preferably lower toward the end in a direction from the inside toward the end in a plan view of the polarizer, from the viewpoint of suppressing cracks and making color loss less noticeable in the appearance of the polarizer. The end of the polarizer preferably does not contain boric acid.

[0015] The length from the end of the low boric acid concentration portion may be, for example, 15 μm or more, and from the viewpoint of suppressing cracks, may be preferably 15 μm or more and less than 200 μm, more preferably 15 μm or more and less than 150 μm, even more preferably 15 μm or more and less than 100 μm, and particularly preferably 15 μm or more and less than 50 μm.

[0016] The boundary between the region where the low boric acid concentration portion is formed and the other region can be obtained from the boric acid concentration profile with respect to the distance from the end obtained by time-of-flight secondary ion mass spectrometry (TOF-SIMS) described in the Examples section below. For example, when a region where the boric acid ion intensity is constant can be read in the boric acid concentration profile, the average value of the boric acid ion intensity of the region can be obtained, and the region from the end to the position where the boric acid ion intensity is the average value can be determined as the low boric acid concentration portion. When the region where the boric acid ion intensity is constant is difficult to read in the boric acid concentration profile, the average value of the boric acid ion intensity in a range of 30 μm inward from the point where the boric acid ion intensity is maximum can be obtained in the boric acid concentration profile, and the region from the end to the position where the boric acid ion intensity is the average value can be determined as the low boric acid concentration portion.

[0017] The polarizer has a low iodine concentration portion formed in a region including the end portion, the iodine concentration being lower than the iodine concentration in an inner region 500 μm or more inward from the end portion. The length of the low iodine concentration portion from the end portion is 19 μm or more and 100 μm or less. As shown in FIG. 3, the polarizer 2 has a low iodine concentration portion 33 in a region including the end portion in a planar view. The iodine concentration of an intermediate region 34 between the low iodine concentration portion 33 and the inner region 32 is usually approximately the same as that of the inner region 32. The low iodine concentration portion is a portion formed in a region through which light passes when the polarizer is observed in a planar view using an optical microscope. Iodine can be, for example, iodine molecules (I2), polyiodine complexes (I3 - , I5 - ), iodine ion (I - ) are included.

[0018] When the length from the end of the low iodine concentration portion is 100 μm or less, the low iodine concentration portion tends to be less noticeable in the appearance of the polarizer. When the length from the end of the low iodine concentration portion is 19 μm or more, cracks tend to be easily suppressed. The length from the end of the low iodine concentration portion is preferably 19 μm or more and 50 μm or less from the viewpoint of making iodine loss less noticeable.

[0019] The low iodine concentration area and the high iodine concentration area are distinguished according to the method described in the Examples section below. In an optical microscope image that is imported into a personal computer and image processed, the low iodine concentration area is usually an area with a brightness of 180 or more, the inner area is 100 to 140, and the iodine concentration brightness of the intermediate area between the low iodine concentration area and the inner area is usually less than 180.

[0020] The low boric acid concentration portion and the low iodine concentration portion may be portions that partially overlap each other, or one of them may be a portion that completely overlaps the other. From the viewpoint of suppressing cracks and making iodine loss less noticeable, it is preferable that the low iodine concentration portion completely includes the low boric acid concentration portion. A plurality of low boric acid concentration sites and a plurality of low iodine concentration sites may be formed in a plurality of regions of the polarizer.

[0021] From the viewpoint of suppressing cracks, the low boric acid concentration portion and the low iodine concentration portion are preferably formed along the outer edge of the polarizer. The low boric acid concentration portion and the low iodine concentration portion may be formed along the entire outer edge of the polarizer, or may be formed along a part of the outer edge of the polarizer.

[0022] The polarizer may have an irregularly shaped portion. In plan view of the polarizer, the irregularly shaped portion may be a concave portion formed on the outer edge and a through hole formed in the polarizer surface. The irregularly shaped portion may have a discontinuous tangent direction, for example, a shape of two straight lines intersecting, and the radius of curvature at the intersection may be 0 mm. When the tangent direction is discontinuous or the radius of curvature at the intersection is small (usually 3 mm or less, preferably 2 mm or less, more preferably 1 mm or less), the effect of preventing cracks according to the present invention is remarkable. The polarizer may have two or more irregularly shaped portions on the outer edge and / or in the plane. Specific examples of the shape and the position of the irregularly shaped portion are the same as those of the irregularly shaped portion described later in the description of the polarizing plate.

[0023] When the polarizer has an irregularly shaped portion, from the viewpoint of suppressing cracks and making the low iodine concentration portion less noticeable, it is preferable that a low boric acid concentration portion and a low iodine concentration portion are formed in an end region included in the irregularly shaped portion. In a polarizer having an irregularly shaped portion, stress tends to concentrate in the irregularly shaped portion and cracks tend to occur easily in a condensation heat shock test. By forming a low boric acid concentration site in an end region included in the irregularly shaped portion, the occurrence of cracks in the condensation heat shock test tends to be easily suppressed. Furthermore, as shown in Fig. 4, when a polarizing plate 21 including a polarizer having an irregularly shaped portion is used in an image display device 20 having a camera hole 22, a cover glass 24, an adhesive layer 25, a liquid crystal panel 23, a polarizing plate 26, a camera 27, and a light-shielding tape 28, the circled portion in Fig. 4 is directly visible, so that the low iodine concentration portion formed in a wide region at the end included in the irregularly shaped portion of the polarizer 21 tends to be noticeable, which may result in a decrease in design. However, even when the polarizer of the present invention is used in an image display device having a camera hole as described above, the low iodine concentration portion tends to be less noticeable and the design tends to be excellent.

[0024] When the irregularly shaped portion is a concave portion, it is preferable from the viewpoint of suppressing cracks that the depth direction of the concave portion and the absorption axis (stretching direction) are formed to be perpendicular to each other, for example. Also, they may be formed to intersect at an angle of 30 degrees or more, usually 60 degrees or less.

[0025] The polarizer may be in the form of a long strip or a sheet. When the polarizer is in the form of a sheet, the polarizer may have a square or rounded square shape in plan view. The rounded square shape refers to a shape in which one or more of the corners of the square are curved, that is, one or more of the corners of the square are rounded, and the square shape refers to a shape in which none of the four corners are rounded. In this specification, the square shape refers to a rectangular shape or a square shape. When the polarizing plate has a rounded square shape, one or more of the four corners of the polarizing plate may be rounded. The polarizer may have a polygonal, circular, or elliptical overall shape in plan view. Specific examples of the overall shape of the polarizer in plan view are the examples of the overall shape of the polarizing plate in the description of the polarizing plate described later.

[0026] The thickness of the polarizer may be, for example, 1 μm or more and 50 μm or less, or 3 μm or more and 15 μm or less. The thinner the polarizer, the easier it is to suppress the shrinkage or expansion of the polarizer itself due to temperature changes, and the easier it is to suppress the change in the dimensions of the polarizer itself. As a result, stress is less likely to act on the polarizer, and cracks in the polarizer tend to be more easily suppressed.

[0027] FIG. 5 shows the overall shape of the polarizer 2 in a plan view. The polarizer 2 has an overall shape of a rounded rectangular shape, and has a concave portion as an irregularly shaped portion. The concave portion is formed so that the depth direction and the absorption axis (stretching direction) are parallel to each other. In the polarizer 2, region I (11) and region II (12) are partially formed along a part of the outer periphery including the concave portion, and are formed on the outer edge including the concave portion. Region I (11) is a region in which both a low boric acid concentration portion and a low iodine concentration portion are formed. Region II (12) can be a region in which either a low boric acid concentration portion or a low iodine concentration portion is formed.

[0028] <Polarizing plate> A polarizing plate according to another aspect of the present invention includes the above-mentioned polarizer and an optical film provided on one or both sides of the polarizer. The optical film can be attached to the polarizer via an adhesive layer made of an adhesive or a pressure-sensitive adhesive.

[0029] 1, a polarizing plate 1 according to this embodiment includes at least a pair of optical films (3, 4) and a film-like polarizer 2 located between the pair of optical films (3, 4). For ease of explanation, the polarizing plate 1 including the polarizer 2 and the pair of optical films (3, 4) will be mainly described below. However, as described later, the number of optical films included in the polarizing plate is not limited to two.

[0030] The optical film refers to a film-like member (excluding the polarizer 2 itself) that constitutes the polarizing plate 1. For example, the optical film implies a protective film and a release film. Each optical film does not have to have a specific optical function by itself. The "film" (optical film) may be referred to as a "layer" (optical layer). Each of the pair of optical films (3, 4) contains a resin. However, the composition of each of the optical films (3, 4) is not limited.

[0031] The polarizer 2 overlaps directly or indirectly with the optical films (3, 4). For example, there may be another optical film between the polarizer 2 and the optical films (3, 4). The polarizer 2 may overlap with the optical films (3, 4) via an adhesive layer.

[0032] Fig. 6 is a top view showing the surface of polarizing plate 1 according to this embodiment. The cross section of polarizing plate 1 shown in Fig. 6 is perpendicular to the surface of polarizing plate 1. In addition, this cross section of polarizing plate 1 is perpendicular to the outer periphery 1p of polarizing plate 1 located inside recess 13 formed in polarizing plate 1.

[0033] As shown in FIG. 6, a recess 13 is formed on the outer periphery 1p of the polarizing plate 1. That is, the outer periphery 1p of the polarizing plate 1 has the recess 13. The recess 13 may be referred to as a depression, a cutout, or a notch. The recess 13 may penetrate the polarizing plate 1 in a direction (Z-axis direction) perpendicular to the surface (light-receiving surface) of the polarizing plate 1. The outer periphery 1p of the polarizing plate 1 may be referred to as the outer edge or contour of the polarizing plate 1 (light-receiving surface) as seen from a direction perpendicular to the light-receiving surface of the polarizing plate 1 (planar view direction).

[0034] The inner corner 13c of the recess 13 may be a right angle or a curved line in top view. That is, the end face of the polarizing plate 1 located at the inner corner 13c of the recess 13 may be a curved surface. That is, the inner corner 13c of the recess may be chamfered. By having the inner corner 13c of the recess 13 be curved in top view, cracks at the inner corner 13c of the recess 13 are more easily suppressed than when the inner corner 13c is a right angle. As shown in FIG. 4, the corners located at both ends of the recess 13 and the corners located at the four corners of the polarizing plate 1 may also be chamfered.

[0035] The width of the recess 13 (the width of the recess 13 in the X-axis direction) is not particularly limited, but may be, for example, 3 mm or more and 160 mm or less. The depth of the recess 13 (the width of the recess 13 in the Y-axis direction) is not particularly limited, but may be, for example, 0.5 mm or more and 160 mm or less. The length of the side (short side) of the polarizing plate 1 on which the recess 13 is formed is not particularly limited, but may be, for example, 30 mm or more and 90 mm or less. The length of the side (long side) of the polarizing plate 1 on which the recess 13 is not formed is not particularly limited, but may be, for example, 30 mm or more and 170 mm or less. The thickness of the entire polarizing plate 1 is not particularly limited, but may be, for example, 30 μm or more and 300 μm or less.

[0036] The recess 13 shown in FIG. 6 is a quadrangle (rectangle) with rounded corners. However, the shape of the recess 13 is not limited. For example, the recess 13 may be a square. The recess 13 may be a polygon other than a quadrangle or a triangle. As shown in (a) to (h) in FIG. 7, the shape of the recess 13 may be a rectangle with rounded corners, a rectangle, a semicircle, a V-shape, a shape combining straight lines and curved lines, or a curved shape. Although the shapes of the polarizing plate 1 shown in (a) to (h) in FIG. 7 are all symmetrical, the shape of the polarizing plate 1 may be asymmetrical. A plurality of recesses 13 may be formed on the outer periphery 1p of the polarizing plate 1. A plurality of recesses 13 may be formed on one side constituting the outer periphery 1p of the polarizing plate 1. The recess 13 may be formed by cutting out at least one of the four corners of the quadrangle-shaped polarizing plate 1.

[0037] The overall shape of the polarizing plate 1 excluding the recesses 13 is approximately quadrangular (rectangular). However, the shape of the polarizing plate 1 is not limited. For example, the shape of the polarizing plate 1 may be square. The shape of the polarizing plate 1 may be a polygon other than a rectangle, a circle, or an ellipse. The overall shapes of the polarizer 2 and the optical films (3, 4) may be approximately the same as the shape of the polarizing plate 1. In the case of the rectangular polarizing plate 1 shown in FIG. 4, the recesses 13 are formed on the short sides of the polarizing plate 1, but the recesses 13 may also be formed on the long sides of the polarizing plate 1.

[0038] 8, the polarizer 1 may have a through hole in the plane when seen in a plan view. The diameter of the through hole may be, for example, 0.5 mm or more and 30 mm or less, and preferably 1 mm or more and 10 mm or less.

[0039] (Another embodiment of the polarizing plate) For example, the polarizing plate may further include another optical film containing a resin in addition to a pair of optical films consisting of the first optical film and the second optical film. That is, the polarizing plate may include three or more optical films. For example, as shown in FIG. 9, the polarizing plate may include a first optical film 3 and a second optical film 4, a polarizer 2 located between the first optical film 3 and the second optical film 4, and a third optical film 15 overlapping the first optical film 3. The third optical film 15 may be overlapped on the first optical film 3 via the above-mentioned adhesive layer. The resin contained in the third optical film 15 may be at least one of the above-mentioned resins listed as the resin contained in each of the first optical film 3 and the second optical film 4. The composition of the third optical film 15 may be the same as the composition of the first optical film 3. The composition of the third optical film 15 may be different from the composition of the first optical film 3. The composition of the third optical film 15 may be the same as the composition of the second optical film 4. The composition of the third optical film 15 may be different from the composition of the second optical film 4. The thickness of the third optical film 15 may be, for example, 5 μm or more and 200 μm or less. The third optical film 15 may be peeled off and removed from the polarizing plate during the manufacturing process of the image display device. In other words, the third optical film 15 may be a temporary optical film.

[0040] The polarizing plate may further include an adhesive layer overlapping one of the pair of optical films and a release film overlapping the adhesive layer. For example, the polarizing plate shown in FIG. 9 may further include an adhesive layer overlapping the second optical film 4 and a release film overlapping the adhesive layer. The adhesive layer may include a pressure-sensitive adhesive such as an acrylic pressure-sensitive adhesive, a rubber pressure-sensitive adhesive, a silicone pressure-sensitive adhesive, or a urethane pressure-sensitive adhesive. The thickness of the adhesive layer may be, for example, 2 μm or more and 100 μm or less. The resin contained in the release film may be at least one of the above resins listed as the resin contained in each of the first optical film 3 and the second optical film 4. The composition of the release film may be the same as the composition of the first optical film 3. The composition of the release film may be different from the composition of the first optical film 3. The composition of the release film may be the same as the composition of the second optical film 4. The composition of the release film may be different from the composition of the second optical film 4. The thickness of the release film may be, for example, 10 μm or more and 100 μm or less. The release film may be peeled off and removed from the polarizing plate during the manufacturing process of the image display device. The release film may be disposed on both sides of the polarizing plate via an adhesive layer.

[0041] The polarizing plate may further include, as an optical film or layer, at least one selected from the group consisting of a reflective polarizing film, a film with an antiglare function, a film with a surface antireflection function, a reflective film, a semi-transmissive reflective film, a viewing angle compensation film, a window film, an antistatic layer, a hard coat layer, an optical compensation layer, a touch sensor layer, and an antifouling layer.

[0042] The polarizing plate may have irregularly shaped portions when viewed from above. The polarizing plate may be rectangular or rectangular with rounded corners when viewed from above.

[0043] (Optical film) The optical film may be a thermoplastic resin having light transmission. The optical film may be an optically transparent thermoplastic resin. The resin constituting the optical film may be, for example, a linear polyolefin resin, a cyclic olefin polymer resin (COP resin), a cellulose ester resin, a polyester resin, a polycarbonate resin, a (meth)acrylic resin, a polystyrene resin, or a mixture or copolymer thereof.

[0044] When the polarizing plate has a first optical film and a second optical film, the composition of the first optical film may be exactly the same as the composition of the second optical film. For example, both the first optical film and the second optical film may contain a cyclic olefin polymer resin (COP resin). Even when the first optical film and the second optical film contain a cyclic olefin polymer resin (COP resin), in the present invention, cracks are easily suppressed and color loss is easily made less noticeable. When the polarizing plate has a first optical film and a second optical film, the composition of the first optical film may be different from the composition of the second optical film.

[0045] The glass transition temperatures of the first optical film and the second optical film are preferably from 100° C. to 200° C., or from 120° C. to 150° C. When the glass transition temperatures of the first optical film and the second optical film are within the above ranges, the first optical film and the second optical film are likely to be fused to each other due to heat generated by polishing the ends of the respective optical films.

[0046] The linear polyolefin resin may be, for example, a homopolymer of a linear olefin such as a polyethylene resin or a polypropylene resin, or a copolymer of two or more types of linear olefins.

[0047] The cyclic olefin polymer resin (cyclic polyolefin resin) may be, for example, a ring-opening (co)polymer of a cyclic olefin or an addition polymer of a cyclic olefin. The cyclic olefin polymer resin may be, for example, a copolymer (for example, a random copolymer) of a cyclic olefin and a chain olefin. The chain olefin constituting the copolymer may be, for example, ethylene or propylene. The cyclic olefin polymer resin may be a graft polymer obtained by modifying the above-mentioned polymer with an unsaturated carboxylic acid or a derivative thereof, or a hydrogenated product thereof. The cyclic olefin polymer resin may be, for example, a norbornene resin using a norbornene monomer such as norbornene or a polycyclic norbornene monomer.

[0048] The cellulose ester resin may be, for example, cellulose triacetate (triacetyl cellulose (TAC)), cellulose diacetate, cellulose tripropionate, or cellulose dipropionate. Copolymers of these may also be used. Cellulose ester resins in which some of the hydroxyl groups have been modified with other substituents may also be used.

[0049] A polyester resin other than the cellulose ester resin may be used. The polyester resin may be, for example, a polycondensation product of a polycarboxylic acid or its derivative with a polyhydric alcohol. The polycarboxylic acid or its derivative may be a dicarboxylic acid or its derivative. The polycarboxylic acid or its derivative may be, for example, terephthalic acid, isophthalic acid, dimethyl terephthalate, or dimethyl naphthalenedicarboxylate. The polyhydric alcohol may be, for example, a diol. The polyhydric alcohol may be, for example, ethylene glycol, propanediol, butanediol, neopentyl glycol, or cyclohexanedimethanol.

[0050] The polyester-based resin may be, for example, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polytrimethylene terephthalate, polytrimethylene naphthalate, polycyclohexane dimethyl terephthalate, or polycyclohexane dimethyl naphthalate.

[0051] A polycarbonate-based resin is a polymer in which polymerization units (monomers) are bonded via carbonate groups. The polycarbonate-based resin may be a modified polycarbonate having a modified polymer skeleton, or may be a copolymer polycarbonate.

[0052] The (meth)acrylic resin may be, for example, a poly(meth)acrylic acid ester (e.g., polymethyl methacrylate (PMMA)); a methyl methacrylate-(meth)acrylic acid copolymer; a methyl methacrylate-(meth)acrylic acid ester copolymer; a methyl methacrylate-acrylic acid ester-(meth)acrylic acid copolymer; a methyl (meth)acrylate-styrene copolymer (e.g., MS resin); or a copolymer of methyl methacrylate and a compound having an alicyclic hydrocarbon group (e.g., a methyl methacrylate-cyclohexyl methacrylate copolymer, a methyl methacrylate-norbornyl (meth)acrylate copolymer, etc.).

[0053] Each of the first optical film and the second optical film may contain at least one additive selected from the group consisting of a lubricant, a plasticizer, a dispersant, a heat stabilizer, an ultraviolet absorber, an infrared absorber, an antistatic agent, and an antioxidant.

[0054] The thickness of the first optical film may be, for example, 5 μm to 90 μm, or 10 μm to 60 μm, and the thickness of the second optical film may also be, for example, 5 μm to 90 μm, or 10 μm to 60 μm.

[0055] At least one of the first optical film and the second optical film may be a film having an optical function. The film having an optical function may be, for example, a retardation film or a brightness improvement film. For example, a retardation film having an arbitrary retardation value can be obtained by stretching a film made of the above-mentioned thermoplastic resin or forming a liquid crystal layer or the like on the film.

[0056] The first optical film may be laminated on the polarizer via an adhesive layer. The second optical film may also be laminated on the polarizer via an adhesive layer. The adhesive layer may contain a water-based adhesive such as polyvinyl alcohol. The adhesive layer may contain an active energy ray curable resin described later.

[0057] The active energy ray curable resin is a resin that is cured by being irradiated with active energy rays. The active energy rays may be, for example, ultraviolet rays, visible light, electron beams, or X-rays. For example, the active energy ray curable resin may be an ultraviolet ray curable resin.

[0058] The active energy ray curable resin may be one type of resin or may contain multiple types of resins. For example, the active energy ray curable resin may contain a cationic polymerizable curable compound or a radical polymerizable curable compound. The active energy ray curable resin may contain a cationic polymerization initiator or a radical polymerization initiator for initiating the curing reaction of the curable compound.

[0059] The cationic polymerizable curable compound may be, for example, an epoxy-based compound (a compound having at least one epoxy group in the molecule) or an oxetane-based compound (a compound having at least one oxetane ring in the molecule). The radically polymerizable curable compound may be, for example, a (meth)acrylic-based compound (a compound having at least one (meth)acryloyloxy group in the molecule). The radically polymerizable curable compound may be a vinyl-based compound having a radically polymerizable double bond.

[0060] The active energy ray-curable resin may contain, as necessary, a cationic polymerization accelerator, an ion trapping agent, an antioxidant, a chain transfer agent, a tackifier, a thermoplastic resin, a filler, a flow adjuster, a plasticizer, an antifoaming agent, an antistatic agent, a leveling agent, a solvent, or the like.

[0061] In order to improve the adhesion between the polarizer and the optical film, prior to bonding of the polarizer and the optical film, the bonding surfaces of the polarizer and / or the optical film may be subjected to surface treatment such as corona treatment, flame treatment, plasma treatment, ultraviolet irradiation treatment, primer coating treatment, and saponification treatment.

[0062] (Other layers) The polarizing plate may further include a front plate, a retardation film (for example, a layer imparting a retardation of λ / 2, a layer imparting a retardation of λ / 4, a positive C layer, and a layer obtained by laminating a combination of at least two layers selected from these), a protective film, a touch sensor panel, an adhesive layer, etc. The polarizing plate can also be used as a circular polarizing plate by laminating a layer imparting a retardation of λ / 4. The polarizing plate may be an adhesive layer-attached polarizing plate.

[0063] <Method of manufacturing polarizing plate> The method for producing a polarizing plate includes a polarizer that is a resin film containing boric acid and iodine and an optical film arranged on one or both sides of the polarizer, and includes a base treatment step of contacting an end of the resin film containing boric acid and iodine with a basic solution at a temperature of 50° C. or less for 6 minutes or less. The method for producing a polarizing plate may further include a polarizer production step (a production step of a resin film containing boric acid and iodine) described below, a lamination step, a molding step, and a cutting step, in this order, before the base treatment step.

[0064] (Polarizer manufacturing process) A resin film containing boric acid and iodine (hereinafter also referred to as an untreated polarizer) can be produced by, for example, subjecting a polyvinyl alcohol-based resin film (PVA film) to a stretching treatment, a dyeing treatment, and a crosslinking treatment. The stretching treatment, the dyeing treatment, and the crosslinking treatment can be carried out by a known method.

[0065] For example, first, the PVA film is stretched uniaxially or biaxially. The dichroic ratio of the uniaxially stretched polarizer tends to be high. Following the stretching, the PVA film is dyed with iodine, a dichroic dye (polyiodine), or an organic dye using a dyeing solution. The dyeing solution may contain boric acid, zinc sulfate, or zinc chloride. The PVA film may be washed with water before dyeing. The washing with water removes dirt and antiblocking agents from the surface of the PVA film. Furthermore, the washing with water swells the PVA film, which tends to suppress dyeing spots (uneven dyeing). The dyed PVA film is treated with a solution of a crosslinking agent containing boric acid (e.g., an aqueous solution of boric acid) for crosslinking. After the treatment with the crosslinking agent, the PVA film is washed with water and then dried. Through the above procedures, a resin film containing boric acid and iodine is obtained. Polyvinyl alcohol (PVA) resins are obtained by saponifying polyvinyl acetate resins. The polyvinyl acetate resin may be, for example, polyvinyl acetate, which is a homopolymer of vinyl acetate, or a copolymer of vinyl acetate and other monomers (for example, ethylene-vinyl acetate copolymer). The other monomers copolymerized with vinyl acetate may be unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, or acrylamides having an ammonium group, in addition to ethylene. The polyvinyl alcohol resin may be modified with aldehydes. The modified polyvinyl alcohol resin may be, for example, partially formalized polyvinyl alcohol, polyvinyl acetal, or polyvinyl butyral. The polyvinyl alcohol resin may be a polyene-based oriented film such as a dehydrated product of polyvinyl alcohol or a dehydrochlorinated product of polyvinyl chloride. Dyeing may be performed before stretching, or stretching may be performed in a dyeing solution. The length of the stretched resin film may be, for example, 3 to 7 times the length before stretching. The polyvinyl alcohol resin film may be in the form of a long strip or a sheet.

[0066] (Lamination process) In the lamination process, the untreated polarizer and the optical film are laminated and bonded to each other to prepare a first laminate. The untreated polarizer and the optical film may be in the form of a long strip. When the untreated polarizer is laminated so as to be disposed between a pair of optical films, as shown in FIG. 10, in the first laminate 10, the untreated polarizer 7 is located between a pair of optical films (5, 9).

[0067] The optical film can be attached to the polarizer via an adhesive layer.

[0068] In the lamination step, a pressure-sensitive adhesive layer can be formed on one of the outermost surfaces of the first laminate 10. The pressure-sensitive adhesive layer can be formed, for example, by applying a pressure-sensitive adhesive to the surface of one of the pair of optical films (5, 9) opposite the unbase-treated polarizer 7 to form a pressure-sensitive adhesive layer, and then laminating a separate film that can be peeled off from the pressure-sensitive adhesive layer thereon. In addition, in the lamination step, a protective film that can be peeled off from the optical film can be laminated to the outermost surface of one of the first laminates 10.

[0069] (molding process) In the molding process, the dimensions of the first laminate 10 may be adjusted to dimensions that are easy to process. Also, an irregularly shaped portion may be formed on the outer edge of the first laminate 10 by punching or cutting. The cutting and / or punching process may be performed by using a cutting blade, a punching blade, or by irradiating a laser beam. The laser beam may be a CO2 laser. The long first laminate may be made into a sheet-like first laminate in the molding process. In the molding step, the first laminate can be cut or punched either alone or in a state where a plurality of sheets are stacked.

[0070] (cutting process) The method for producing a polarizing plate may further include a cutting step of contacting an end mill with the periphery of the first laminate or the second laminate described later and moving the end mill along the periphery of the laminate. As shown in Fig. 10, the positions of the ends of the unbase-treated polarizer 7 and the optical films (5, 9) may be aligned over the entire periphery of the first laminate 10 before the cutting step.

[0071] As shown in FIG. 11 and FIG. 12, the end mill 50 used in the cutting process has a blade (edge) 50e that protrudes from a side surface that is approximately parallel to the rotation axis 50a. In the cutting process, the side surface of the end mill 50 is brought into contact with the outer periphery (end surface) of the first laminate 10, and the rotating end mill 50 is moved along the outer periphery of the first laminate 10. For example, the rotating end mill 50 may be moved along a path indicated by an arrow in FIG. 12. As a result, the outer periphery (end surface) of the first laminate 10 is cut or polished by the blade 50e, the outer periphery (end surface) of the first laminate 10 is smoothed, a concave portion 13 is formed, and the inner corner of the concave portion 13 is chamfered. As shown in FIG. 11, after a plurality of first laminates 10 are stacked to form a second laminate 100, the side surface of the end mill 50 may be brought into contact with the outer periphery (end surface) of the second laminate 100, and the rotating end mill 50 may be moved along the outer periphery of the second laminate 100. That is, in the cutting step, the outer peripheries of the multiple first laminates 10 constituting the second laminate 100 may be cut or polished collectively with an end mill 50. In the cutting step, the corners located at both ends of the recessed portion 13 and the corners located at the four corners of the first laminate 10 may be chamfered.

[0072] The cutting amount of the end mill in the cutting step may be, for example, 10 μm or more and 500 μm or less, and preferably 50 μm or more and 150 μm or less.

[0073] The cutting step may be repeated three or more times. For example, in the third cutting step, the first laminate 10 may be almost completely cut, and the chips generated in the second cutting step may be removed from the end surface of the first laminate 10. In each cutting step, a plurality of end mills may be used.

[0074] The feed rate of the end mill in the cutting process may be 100 mm / min or more and less than 3000 mm / min. The rotation speed of the end mill in the cutting process may be, for example, 500 rpm or more and 60000 rpm or less, preferably 10000 rpm or more and 60000 rpm or less. The cutting angle in the cutting process may be, for example, 30° or more and 70° or less, preferably 45° or more and 65° or less. When the twist angle of the end mill 50 is α, the cutting angle β is defined as 90°-α. As shown in FIG. 11, the twist angle α of the end mill 50 is the angle between the direction d1 in which the blade 50e extends on the side of the end mill 50 and the rotation axis 50a of the end mill 50. The cutting angle β may be rephrased as the angle between the direction d1 in which the blade 50e extends and the direction d2 perpendicular to the rotation axis 50a. The diameter φ (thickness) of the end mill 50 used in the cutting step may be, for example, not less than 3.0 mm and not more than 6.0 mm.

[0075] (Base treatment step) The base treatment can be carried out by contacting the end of the resin film containing boric acid and iodine contained in the first laminate with a basic solution. By carrying out the base treatment on the end of the resin film containing boric acid and iodine, a low boric acid concentration portion and a low iodine concentration portion can be formed. The base treatment can be carried out on the second laminate, which is made by stacking, for example, 5 to 3000 sheets of the first laminate. The number of sheets of the first laminate to be stacked is preferably 7 or more, for example, 2000 sheets or 1000 sheets.

[0076] The basic solution used in the base treatment preferably contains water. The basic solution may be, for example, a solution in which a strongly basic compound is dissolved in a solvent, and is preferably an aqueous solution of a strongly basic compound. The strongly basic compound preferably contains sodium hydroxide and / or potassium hydroxide.

[0077] The temperature of the basic solution to be brought into contact with the end of the resin film containing boric acid and iodine may be 50°C or less, which suppresses deterioration of optical performance (reduction in polarization degree, change in hue, etc.) due to disturbance in the orientation of the polarizer in the polarizing plate, and is preferably 45°C or less, more preferably 40°C or less, from the viewpoint of reducing the boric acid concentration, and is usually a temperature above room temperature.

[0078] The time for contacting the end of the resin film containing boric acid and iodine with the basic solution may be within 6 minutes, which suppresses deterioration of optical performance (reduction in polarization degree, change in hue, etc.) due to disturbance in the orientation of the polarizer in the polarizing plate, and is preferably within 5 minutes from the viewpoint of reducing the boric acid concentration, and is usually more than 1 minute.

[0079] The concentration of the basic compound in the basic solution may be, for example, 0.1 mol / L or more and 4 mol / L or less, preferably 1 mol / L or more and 3 mol / L or less, and more preferably 1.5 mol / L or more and 2.5 mol / L or less.

[0080] Examples of methods for contacting the end of the resin film containing boric acid and iodine with a basic solution include a method of immersing all or a part of the first laminate or the second laminate in a tank containing the basic solution, and a method of spraying the basic solution onto all or a part of the first laminate or the second laminate.

[0081] After contacting with the basic solution, the resin film containing boric acid and iodine can be washed with water. It is preferable to wash with water at least twice. The washing with water can be performed, for example, by immersing the first laminate or the second laminate in a tank containing water and / or by spraying water on the first laminate or the second laminate.

[0082] By the above method, the polarizing plate according to this embodiment is obtained.

[0083] <Image display device> The polarizing plate described above can be used in an image display device. Examples of the image display device include a liquid crystal display device and an organic EL display device. The polarizing plate may be used as a polarizing plate arranged on the viewing side of the image display device, may be used as a polarizing plate arranged on the backlight side of the image display device, or may be used as a polarizing plate on both the viewing side and the backlight side. Since the polarizing plate of the present embodiment is less noticeable in the color-depleted areas, even when used on the viewing side of the image display device, the design is less likely to be impaired. Therefore, the image display device is suitable as an image display device having a camera hole, for example, an image display device used in mobile devices such as smartphones and mobile phones, and personal computers. EXAMPLES

[0084] The present invention will be described in more detail below with reference to examples. In the examples, "%" and "parts" are by mass % and parts by mass unless otherwise specified.

[0085] [Condensation heat shock test] For each of the Examples and Comparative Examples, three polarizing plates were tested according to the following procedures. (1) The surface of the polarizing plate on which the optical film having a thickness of 21 μm was placed was attached to the surface of a glass plate (manufactured by Corning) that had been wiped with ethanol via an adhesive layer, and autoclaved (50° C., 0.5 MPa, 20 minutes). (2) After autoclaving, it was confirmed by observation with an optical microscope that no cracks had occurred in two corner edge regions of the concave portion of the polarizing plate (areas circled in FIG. 15). (3) The polarizing plate was placed in a condensation heat shock oven, and the following procedure was repeated 10 times, with each cycle consisting of the following steps: First, the polarizing plate was held at -40°C for 30 minutes and cooled. It was then exposed to 25°C outside air for 5 minutes. It was then heated to 85°C and held under 85°C dry conditions for 30 minutes. It was then cooled to 25°C, held for 5 minutes, and then cooled to -40°C. Note that when exposed to 25°C outside air for 5 minutes, condensation formed on the surface of the polarizing plate, and it was then heated to 85°C in the condensed state. After being held under 85°C dry conditions, the condensation had disappeared from the polarizing plate. (4) The polarizing plate was removed from the condensation heat shock oven, and the number, average length, and maximum length of the cracks were measured using an optical microscope at the two corners of the recessed portion observed using the optical microscope in (2) above. In addition, the distance from the edge of the polarizing plate to the area where the low iodine concentration area was formed was measured using an optical microscope.

[0086] [Measurement of boric acid concentration] Time-of-flight secondary ion mass spectrometry (TOF-SIMS) was used to measure borate ions (BO3 3- 13, the protective film attached to the optical film 5 (thickness 52 μm) side of the polarizing plate 110 was peeled off, the separate film attached to the adhesive layer on the optical film 9 (thickness 21 μm) side was peeled off, and one end region including the corner of the recessed portion was cut out to a length of 1 mm (1000 μm) with a width of 100 μm toward the inside of the polarizing plate to obtain a measurement sample 200. The measurement sample 200 had an optical film 201 (thickness 52 μm), an adhesive layer 202 (thickness 1 μm), a polarizer 203 (thickness 8 μm), an adhesive layer 204 (thickness 1 μm), an optical film 205 (thickness 21 μm), and an adhesive layer 206 (thickness 20 μm) in this order. The ion beam was irradiated while scanning a measurement region 207 on the side surface in the longitudinal direction (1000 μm) of the measurement sample 200, a two-dimensional distribution of the signal intensity of borate ions on this side surface was obtained, a portion corresponding to the polarizer side surface was cut out from the obtained two-dimensional distribution, and the integrated value of the signal intensity was plotted against the longitudinal direction of the measurement sample 200 to obtain a profile of the borate concentration against the longitudinal direction. The conditions for time-of-flight secondary ion mass spectrometry (TOF-SIMS) are shown below. The boric acid concentration was measured in the polarizing plate state, but the obtained boric acid concentration can be regarded as the boric acid concentration of the polarizer. Device name: Product name: PHI TRIFT V nano TOF (ULVAC-PHI, Inc.) Primary ion irradiated: Au3 + Primary ion acceleration voltage: 30 kV Spatial resolution of ion beam: 1μm×1μm Measurement area: 200μm×200μm From the obtained boric acid concentration profile, the average value of the boric acid ion strength in the range of 30 μm or more and 60 μm or less away from the edge was calculated, and the area from the edge to the position where the boric acid ion strength reached the above average value was defined as the low boric acid concentration area, and the length of the area where the low boric acid concentration area was formed from the edge of the polarizing plate (the length of the low boric acid concentration area) was measured.

[0087] [Evaluation of areas with low iodine concentrations] The base-treated portion of the polarizing plate was observed using transmitted light under an optical microscope, and the optical microscope image was imported into a personal computer. The length of the region in which the low iodine concentration portion was formed from the edge of the polarizing plate (the length of the low iodine concentration portion) was measured as follows. In the optical microscope image imported into a personal computer, the low iodine concentration area appears bright to the naked eye, and the inner area appears dark. The optical microscope image was processed and converted into a 256-level black-and-white image (brightness 255 is white and 0 is black) so that the brightness of the low iodine concentration area was 180 to 220 and the brightness of the inner area was 100 to 140. The area with a brightness of 180 or more (white) was determined as the low iodine concentration area, and the average length from the edge was calculated.

[0088] [Preparation of polarizing plate] (First laminate) The preparation of the first laminate 10 will be described with reference to FIG. 14. The first laminate 10 was formed by bonding a pair of optical films 5 and 9 to a polarizer 7 via adhesive layers 6 and 8. The first laminate 10 had a rectangular shape. In the first laminate 10, the polarizer 7 was disposed between the pair of optical films 5 and 9. Both of the pair of optical films 5 and 9 were made of a cyclic olefin polymer resin. The polarizer 7 was a stretched and dyed film-like polyvinyl alcohol.

[0089] An adhesive was applied to the optical film 9 side of the first laminate 10 to form an adhesive layer 41, and a separate film 42 was laminated thereon. This separate film was peelable from the adhesive layer. A protective film 43 was laminated to the optical film 5 side of the first laminate 10. This protective film 43 was peelable from the optical film 5.

[0090] The optical film 5 attached to one surface of the polarizer had a thickness of 52 μm. The optical film 9 attached to the other surface of the polarizer had a thickness of 21 μm. The polarizer 7 had a thickness of 8 μm. The first laminate 10 had a total thickness of 103 μm. The adhesive layer 6 interposed between the optical film 5 having a thickness of 52 μm and the polarizer 7 was a polyvinyl alcohol-based resin (water-based glue). The adhesive layer 8 interposed between the optical film 9 having a thickness of 21 μm and the polarizer 7 was a UV-curable epoxy resin.

[0091] (Deformed processing) According to the above procedure, 47 first laminates 10 were prepared by forming an adhesive layer 41 on the optical film 9 side, laminating a separate film 42 thereon, and laminating a protective film 43 on the optical film 5 side. Each of the first laminates was punched with a Thomson blade to form a concave portion on the short side. The shape of the concave portion was the same in all 47 first laminates. A second laminate was produced by stacking the 47 first laminates with the concave portions formed thereon. In this second laminate, the long and short sides of all 47 first laminates were aligned, and the concave portions were aligned.

[0092] After punching, the following three cutting steps were carried out. In each cutting step, the second laminate was fixed by a clamp, and the side of the end mill was brought into contact with the outer periphery (end face) of the second laminate, while the rotating end mill was moved along the outer periphery (outer periphery including the recessed portion) of the second laminate. In other words, the entire outer periphery of each of the 47 first laminates was cut all at once by the end mill. The end mill used in each cutting step was DXL-4 manufactured by NS Tool Co., Ltd. The cutting angle β was the value shown in Table 1 below. The diameter φ of the end mill was 4 mm.

[0093] The amount of material removed in the first cutting step was the value shown in Table 1 below. The rotation speed (R) of the end mill in the first cutting step was 30,000 rpm. The feed speed (V) of the end mill in the first cutting step was 1,000 mm / min.

[0094] The amount of material removed in the second cutting step was the value shown in Table 1 below. The rotation speed (R) of the end mill in the second cutting step was 30,000 rpm. The feed speed (V) of the end mill in the second cutting step was 1,000 mm / min.

[0095] The amount of material removed in the third cutting step was as shown in Table 1. The rotation speed (R) of the end mill in the third cutting step was 30,000 rpm. The feed speed (V) of the end mill in the third cutting step was 1,000 mm / min.

[0096] By the above method, 47 polarizing plates were produced. The polarizing plates had the same shape, dimensions, and laminated structure. The overall shape of each polarizing plate was rectangular. FIG. 15 shows the shape of the obtained polarizing plate 110 in plan view. As shown in FIG. 15, the polarizing plate 110 had a rectangular recessed portion 113 formed on its short side. The length of the short side of the polarizing plate 110 was 70 mm. The length of the long side of the polarizing plate 110 was 140 mm. The width 111 of the recessed portion 113 was 30 mm. The depth 112 of the recessed portion 113 was 5 mm. The depth direction of the recessed portion 113 was parallel to the absorption axis (stretching direction).

[0097] <Example 1> Ten polarizing plates processed into the above shape were stacked, and the edges were subjected to a base treatment under the following conditions and procedures, thereby obtaining a polarizing plate of Example 1. (1) The sample was immersed in a 2 mol / L NaOH aqueous solution at 40°C for 5 minutes. (2) The laminated polarizing plates were then washed in water washing tank 1 (20° C.) and then in water washing tank 2 (20° C.) for 1 minute each. After the above-mentioned edge base treatment, the boric acid concentration of the three polarizing plates was measured and a condensation heat shock test was performed. The results are shown in Table 1. Figure 16 shows the TOF-SIMS analysis result (a) and an optical microscope image of the edge region (b). This polarizing plate had a low boric acid concentration area formed in a region including the edge, with a width of 20 μm from the edge, and also had a low iodine concentration area formed in a region including the edge, with a width of 50 μm from the edge.

[0098] <Comparative Example 1> For the three polarizing plates processed into the above shapes, boric acid concentration was measured and a condensation heat shock test was performed without carrying out the edge base treatment of Example 1. The results are shown in Table 1. In addition, Figure 17 shows the TOF-SIMS analysis result (a) and an optical microscope image of the edge region (b). In this polarizing plate, a low boric acid concentration portion was formed in a region including the edge portion with a width of 12 μm from the edge portion, and in this polarizing plate, a low iodine concentration portion was not formed in the region including the edge portion.

[0099] <Comparative Example 2> A polarizing plate of Comparative Example 2 was obtained in the same manner as in Example 1, except that the polarizing plate was immersed in the NaOH aqueous solution for 1 minute instead of 5 minutes in Example 1. In addition, Fig. 18 shows the TOF-SIMS analysis result (a) and an optical microscope image of the edge region (b). This polarizing plate had a low boric acid concentration area formed in the region including the edge, with a width of 14 μm from the edge, and also had a low iodine concentration area formed in the region including the edge, with a width of 18 μm from the edge.

[0100] [Table 1]

[0101] In Example 1, the number of cracks was small, the average crack length and the maximum crack length were short, and the region where the low iodine concentration portion was formed was very small. In Comparative Example 1, the number of cracks was large, and the average crack length and maximum crack length were both long, meaning that crack generation was not suppressed. In Comparative Example 2, although the number of cracks was reduced, the average crack length and the maximum crack length were long, and cracks were not sufficiently suppressed. It is clear that according to the present invention, a polarizer can be obtained in which the occurrence of cracks is suppressed in the above-mentioned condensation heat shock test and iodine loss is not noticeable. [Explanation of symbols]

[0102] 1 polarizing plate, 2 polarizer, 3 first optical film, 4 second optical film, 5,9 optical film, 7 non-base-treated polarizer, 10 first laminate, 11 region I, 12 region II, 13,113 concave portion, 14 through hole, 15 third optical film, 20 image display device, 21 polarizing plate, 22 camera hole, 23 liquid crystal panel, 24 cover glass, 25 adhesive layer, 26 polarizing plate, 27 camera, 28 light-shielding tape, 30 boric acid low concentration area, 31 middle area, 32 inner area, 33 iodine low concentration area, 34 middle area, 41 adhesive layer, 42 separate film, 43 protective film, 50 end mill, 50a rotation axis, 50e blade (edge), 100 second laminate, 110 polarizing plate, 111 width, 112 Depth, 200 Measurement sample, 201, 205 Optical film, 202, 204 Adhesive layer, 203 Polarizer, 206 Pressure-sensitive adhesive layer, 207 Measurement area, α Twist angle, β Cutting angle

Claims

1. A polarizer which is a resin film containing boric acid and iodine, A recessed portion is provided on a peripheral portion in a plan view, A low-concentration boric acid portion having a concentration of boric acid lower than the concentration of boric acid in an inner region 500 μm or more inward from the end portion is formed in a region including the end portion in a plan view; The low boric acid concentration portion is formed in a region of 20 μm or more and less than 50 μm inward from the end portion in the plan view, A low iodine concentration portion having an iodine concentration lower than the iodine concentration in the inner region is formed in a region including the end portion, The length from the end of the low iodine concentration portion is 50 μm or more and 100 μm or less, The depth direction of the recess and the absorption axis of the polarizer are perpendicular to each other or intersect at an angle of 30 degrees or more and 60 degrees or less.

2. The polarizer according to claim 1 , wherein the concentration of boric acid in the low boric acid concentration portion decreases toward the end in a direction from the inside toward the end in a plan view of the polarizer.

3. The polarizer according to claim 1 , wherein the low boric acid concentration regions and the low iodine concentration regions are formed along an outer edge of the polarizer.

4. The polarizer according to any one of claims 1 to 3, wherein the low boric acid concentration portion and the low iodine concentration portion are formed in an end region included in the concave portion.

5. A polarizing plate comprising the polarizer according to any one of claims 1 to 4 and an optical film disposed on one or both sides of the polarizer.

6. An image display comprising the polarizing plate according to claim 5 .

7. The image display device according to claim 6, further comprising a camera hole.

Citation Information

Patent Citations

  • Polarizer, polarizing plate and production method of the polarizer

    JP2016206641A

  • Polarizing film with adhesive layer, optical member, and image display device

    JP2017058519A

  • Polarizing plate and method for manufacturing the same

    JP2018025798A

  • Method for manufacturing optical film, optical film, and device for manufacturing optical film

    WO2012053428A1